2016
DOI: 10.1002/jemt.22793
|View full text |Cite
|
Sign up to set email alerts
|

Antheraea pernyi silk sericin mediating biomimetic nucleation and growth of hydroxylapatite crystals promoting bone matrix formation

Abstract: Bone biomineralization is well-regulated processes mediated by extracellular matrix proteins. The materials that can direct nucleation of hydroxylapatite (HAp) crystals and assembly of well-structured material-minerals complex are the key to mimicking the natural mineralization. This study used sericin from Antheraea pernyi (A.pernyi), non-mulberry silkworm cocoon as template to mediate nucleation of HAp crystals. Here we find out that AS (Antheraea pernyi sericin) can nucleate the formation HAp crystals in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Furthermore, the follow‐up applications include the degradable and flexible electronics . Ap silk sericin solution, obtained after autoclave method (121 °C for 30 min), can be used directly or cast into films . The controllable degradability and biocompatibility of silk sericin materials with underlying substrates can yield novel functional systems.…”
Section: Processing Methodologies and Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the follow‐up applications include the degradable and flexible electronics . Ap silk sericin solution, obtained after autoclave method (121 °C for 30 min), can be used directly or cast into films . The controllable degradability and biocompatibility of silk sericin materials with underlying substrates can yield novel functional systems.…”
Section: Processing Methodologies and Biomedical Applicationsmentioning
confidence: 99%
“…Ap sericin is envisioned as a functional template for HAp mineralization . Ap‐sericin/HAp biomaterials not only stimulated the growth of human bone marrow‐derived stem cells (hBMSCs), but also facilitated the osteogenic differentiation and bone mineralization .…”
Section: Processing Methodologies and Biomedical Applicationsmentioning
confidence: 99%
“…In refs , , and , it was shown that sericin can induce the formation of spherical and amorphous HAp crystals in SBF. The obtained crystals exhibit poor crystallinity and preferential growth along the c -axis. , However, in the work of Takeuchi et al, it was found that the preparation conditions of sericin (extraction and storage) influenced HAp deposition in the sericin film. HAp deposition under biomimetic conditions did not occur in all sericin films, being only observed in the sericin solution with the highest content of β-sheet structure.…”
Section: Sericinmentioning
confidence: 99%
“…Also, the very same soluble sericin extracted from native silk fibers was considered in BTE for its ability to mediate the formation of HA crystals in SBF, in turn stimulating adhesion, proliferation, and osteogenic differentiation of human BM-MSCs (Yang et al, 2014;Jiayao et al, 2017).…”
Section: Biocomposites Particles and Chemical Modificationmentioning
confidence: 99%